2019
DOI: 10.1155/2019/1639854
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Their Potential Use in Monitoring Cancer Progression and Therapy: The Contribution of Proteomics

Abstract: Extracellular Vesicles (EVs) are small membrane-enclosed particles released by cells and able to vehiculate information between them. The term EVs categorizes many and different vesicles based on their biogenesis and release pathway, such as exosomes (Exo), ectosomes, or shedding microvesicles (SMVs), apoptotic blebs (ABs), and other EVs subsets, generating a heterogeneous group of components able to redistribute their cargo into the entire organism. Moreover EVs are becoming increasingly important in monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 129 publications
(287 reference statements)
0
65
0
Order By: Relevance
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…These vehiculate enzymes involved in glucose, glutamine and amino acid metabolism, mitochondrial constituents, mitochondria-derived vesicles [92], and genomic/mitochondrial DNA from the tumor of origin [93]. Oncosomes may therefore modulate the metabolic and genetic potential of their target cells; additionally, they may confer proteolytic activity, promoting invasion/migration, and may influence organotropic metastatic spread [34,35,94], a process that may involve integrin signaling [34].…”
Section: Microvesicles and Apoptotic Bodiesmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that EVs may have strong effects on their target cells [2,24]. Therefore, EVs have been described as key players of inter-cellular crosstalk and have been implicated in a variety of mechanisms, such as signal transduction, metastasis development, and even fetal-maternal interactions [3][4][5]7,[25][26][27][28].…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…Microvesicles have procoagulant roles and represent a form of secretion for IL1b. e function of MVs has also been proposed in the rheumatoid arthritis pathogenesis, as well as in the mechanisms associated with tumour proinvasive characteristics and in the induction of oncogenic cellular transformation and fetomaternal communication [43,52,53].…”
Section: Role Of the Extracellular Vesicles In The Cross-talk Among Gmentioning
confidence: 99%
“…Several studies refer to a network of the EVs-mediated cellular interactions linked to cancer spreading [10,52,53] with a prion-like model. Extracellular vesicles originated by cancer cells induce tumour-promoting effects in nearby cells [66], releasing not only soluble factor and proteins, such as oncoproteins, ephrins, and chemokine receptors but also DNA, mRNAs, miRNAs, and other small noncoding RNAs that mediate specific signalling machineries related to dysregulated cell growth and hypoxic environment development [45,[67][68][69][70][71][72].…”
Section: Role Of the Extracellular Vesicles In The Cross-talk Among Gmentioning
confidence: 99%